Use of indwelling pleural catheters for chronic pleural infection. - Davies, H; Rahman, N; Parker, R; Davies, R (2008)
Recurrent, chronic pleural infection creates difficult management issues. Surgical drainage is currently recommended for patients who have failed initial "medical treatment" (ie, tube thoracostomy and antibiotic therapy), but the options for patients not fit for surgery are limited. Prolonged closed tube drainage may be an option in this group, although concerns exist regarding the efficacy and risk of catheter blockage. Long-term indwelling pleural catheters are increasingly used for the treatment of recurrent malignant pleural effusion. Pleural infection is recognized as a complication and is cited as a contraindication to insertion of an indwelling pleural drain within the product literature. We report two patients with empyema in a fixed pleural space in whom the insertion of an ambulatory catheter produced successful drainage. Long-term indwelling pleural catheters may have a role in maintaining the drainage of a chronically infected pleural space that is not readily treated in other ways.